UPAYA PEMBERDAYAAN OLEH PEMERINTAH BAGI PENGRAJIN PERALATAN RUMAH TANGGA BERBAHAN ALUMINIUM (STUDI: DESA TANJUNG ATAP KABUPATEN OGAN ILIR) - Ayu Wandira; Azizah Husin; Ardi Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the empowerment efforts carried out by the government for household appliance artisans using aluminum in Tanjung Atap Village, Ogan Ilir Regency. This research employs a qualitative approach with a descriptive method. The research subjects consist of five individuals: the village head, the head of the artisans, and three household appliance artisans working with aluminum in Tanjung Atap Village. The findings indicate that the government’s empowerment efforts follow three community empowerment indicators. In the potential development indicator, artisans have received socialization from the head of the artisans, students from PGRI University Palembang and Sriwijaya University, as well as training from the Provincial Government of South Sumatra and the Department of Industry and Trade regarding casting techniques, shaping, finishing, and raw material recycling. In the business strengthening indicator, artisans receive assistance in the form of personal protective equipment (PPE) and access to funding through a savings and loan system managed by the village government. In the business protection indicator, artisans receive support in marketing and promotion through annual exhibitions organized by the Ogan Ilir Regency Government, local village events, and social media promotion facilitated by the Department of Industry and Trade.